QZSS L1 Bandwidth Frequency Filter Design for QZSS Receiver - Narumol Onanong; Julongkorn Pattameak; Teerachet Mekpradab; Surachet chinnapark; Prasert Kenpankho (ASEAN Journal of Science and Engineering, 2021)
We present the design of bandpass filter on the frequency of the QZSS satellite, by providing bandwidth at the cut-off frequency equally to the bandwidth of the QZSS L1 with selecting the response characteristic on Butterworth maximally flat amplitude. Bandpass filter design using frequency of the QZSS L1 with bandwidth is 24MHz. The design procedure involves two steps, the first step is to find the required order of the filter, which we use 3rd order, and the second step is to find the scale factor that must be applied to the normalized parameter values. The Band-Pass Butterworth filler is a combination between low pass and high pass. For the Butterworth filter, the value of a resistor that has been used are 50Ω. Then go to find the capacitor and inductor and by using PSpice as the tools for the simulation. The results of the output of bandpass filter at -3dB was between 1563 and 1587MHz. And was bandwidth around 24MHz. The combination of the lowpass filter and high pass filter is to perform as the bandpass filter. Therefore, there are two combinations also in designing bandpass filter. The aim of this combination is to have an influence on the performance of bandpass filter. As a conclusion, this designed filter on the frequency of QZSS L1 is to be useful by using bandpass filter.